2020
DOI: 10.1101/2020.06.14.20131383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for a pervasive autobiographical memory impairment in Logopenic Progressive Aphasia: clinical and neural correlates

Abstract: Logopenic Progressive Aphasia is a rare language disorder characterised by repetition and naming difficulties, reflecting the progressive degeneration of left-lateralized peri-sylvian temporal and inferior parietal regions. Mounting evidence suggests that cognitive impairments in this syndrome extend beyond the language domain to include episodic encoding and retrieval disturbances. To date, it remains unknown whether autobiographical memories from across the lifespan are also subject to decline, yet this info… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…Significant socioemotional dysfunction including loss of empathy and impaired emotion detection abilities has also been documented ( Hazelton et al , 2017 ; Multani et al , 2017 ; Fittipaldi et al , 2019 ). Finally, LPA patients demonstrate significant verbal episodic and autobiographical memory difficulties ( Butts et al , 2015 ; Casaletto et al , 2017 ; Win et al , 2017 ; Eikelboom et al , 2018 ; Ramanan et al , 2020 a ) comparable to that observed in typical Alzheimer’s disease ( Ramanan et al , 2016 ; Ramanan et al , 2020 a , b ). While such deficits could manifest simply as a by-product of language and lexical retrieval difficulties in LPA, compromised performance on tasks with minimal language demands suggests otherwise.…”
Section: Introductionmentioning
confidence: 82%
“…Significant socioemotional dysfunction including loss of empathy and impaired emotion detection abilities has also been documented ( Hazelton et al , 2017 ; Multani et al , 2017 ; Fittipaldi et al , 2019 ). Finally, LPA patients demonstrate significant verbal episodic and autobiographical memory difficulties ( Butts et al , 2015 ; Casaletto et al , 2017 ; Win et al , 2017 ; Eikelboom et al , 2018 ; Ramanan et al , 2020 a ) comparable to that observed in typical Alzheimer’s disease ( Ramanan et al , 2016 ; Ramanan et al , 2020 a , b ). While such deficits could manifest simply as a by-product of language and lexical retrieval difficulties in LPA, compromised performance on tasks with minimal language demands suggests otherwise.…”
Section: Introductionmentioning
confidence: 82%
“…With increasing task difficulty, however, higher‐level visuospatial attentional demands are likely to be subserved by dorsolateral prefrontal structures [32,34]—regions potentially more compromised in lv‐PPA, nfv‐PPA and AD than in sv‐PPA [4]. We note, however, that no single region modulates visuospatial working memory performance [33] and frontotemporoparietal white matter dysconnectivity likely also contribute to the attentional, memory and high‐level visuospatial deficits of PPA and AD [29,38].…”
Section: Discussionmentioning
confidence: 99%